Compound-specific isotopic analysis to characterize the photocatalytic reaction of TiO2 nanoparticles with diethyl phthalate. (November 2022) - Min, Ning; Yao, Jun; Amde, Meseret; Li, Hao; Pang, Wancheng; Zhu, Junjie; Cao, Ying; Richnow, Hans Hermann
Abstract: In this study compound-specific isotope analysis (CSIA) has been used to explore the degradation mechanism of nano titanium dioxide (TiO2 ) catalyzes photodegradation of diethyl phthalate (DEP). TiO2 is a popular photosensitizer with potential in waste water treatment and application in advanced oxidation processes. The degradation process of DEP can be described with a first-order kinetics in the applied concentration ranges. The larger degradation rate constant has been found at neutral conditions. The 13 C and 2 H isotope fractionation associated with the nano TiO2 catalyzes photodegradation of DEP at pH 3, 7 and 11 yield normal isotope effects. In the TiO2 /UV/DEP and TiO2 /H2 O2 /UV/DEP systems, the correlation of 13 C and 2 H fractionation (Λ) were calculated to be 2.7 ± 0.2, 2.8 ± 0.2 at pH 3, 2.2 ± 0.4, 2.5 ± 0.2, 2.3 ± 0.6 at pH 7 and 2.6 ± 0.3, 2.2 ± 0.3, 2.7 ± 0.2 and 2.3 ± 0.3 at pH11, respectively. The dominant free radical species in studied systems were explored by combining free radical quenching method and electron paramagnetic resonance analysis. The hydroxyl radicals have been found as the main radical species at all pH conditions studied. Furthermore, the 13 C and 2 H fractionation suggested that the addition of OH on the benzene ring of DEP is the main conversion pathway. Therefore, CSIA is a promising technology for the identification of reaction pathways of DEP for example in water treatment systems. Graphical abstract: Image 1 Highlights: In UV/nano-TiO2 system, DEP degradation rate is fastest under neutral conditions, and the slowest in alkaline conditions. OH were the dominant free radicals in all systems and pH conditions. εC, εH and Λ values of DEP indicate C-H bond cleavage. The mechanism of .OH reaction with DEP tended to be radical addition to aromatic ring under all conditions.